Analysis of the Effect of Self-Efficacy, Family Support, and Trust on Patient Control Discipline - Galih Duta Prihadi; Sentot Imam Suprapto (Budapest International Research and Critics University, 2022)
The purpose of this study to discuss about analysis of the effect of self-efficacy, family support, and trust on patient control discipline. The design of this study is an observational quantitative study with a cross sectional approach with the focus of the research directed at analyzing the effect of self-efficacy, family support, and trust on discipline control of hypertension patients in the Prolanis Program at the Salsabila Medika Clinic, Kediri City. The total population of 164 respondents and a sample of 116 respondents were taken by using simple random sampling technique. The analytical method uses multiple linear regression analysis. The research results show that almost half of the respondents had moderate self-efficacy as many as 47 respondents (40.5%). Almost half of the respondents have sufficient family support as many as 47 respondents (40.5%). Almost half of respondents have confidence in drugs in the moderate category as many as 48 respondents (41.4%). Most of the respondents were not disciplined in controlling hypertension in the Prolanis Program as many as 85 respondents (73.3%). Based on the results of multiple linear regression analysis shows that with a p-value of 0.000<0.05 then H1 is accepted so it can be concluded that simultaneously there is an effect of self-efficacy, family support, and trust on discipline control of hypertension patients in the Prolanis Program at the Salsabila Medika Clinic, Kediri City with the magnitude of the influence is 84.2%.